Phosphate adsorbed on Fe(III) modified montmorillonite: Surface complexation studied by ATR-FTIR spectroscopy - Borgnino Bianchi, Laura Carolina (2010)
This work is aimed at determining phosphate speciation at the Fe(III)-modified montmorillonite/aqueous solution interface by attenuated total reflectance (ATR-FTIR) spectroscopy. IR spectra are analyzed by second derivative and Fourier self-deconvolution procedures to reveal the number and positions of overlapped bands related to phosphate surface complexes. Experiments are conducted at pH 4.5, 7.0 and 9.0 in order to determine the effects of changing pH on the surface speciation. The molecular view offered by the ATR-FTIR measurements is complemented by macroscopic adsorption data, such as adsorption isotherms and electrophoretic mobilities. The ATR-FTIR spectral analyses reveal the existence of two inner-sphere complexes when phosphate adsorbs on modified montmorillonite, as also suggested from macroscopic adsorption data. The complex coordination depends on the pH. At pH 4.5, both complexes present C2V symmetry or lower. On the other hand, at pH 7.0 and 9.0 one of them is also C2V or lower while the other one presents C3V symmetry. Adsorbed phosphate is not associated with montmorillonite itself but with Fe(III) (hydr)oxides coatings. Therefore, the clay acts as a carrier or support of the Fe(III)-(hydr)oxides, and these coatings are responsible for phosphate adsorption.